Ismail Raji Al-Faruqi's Concept of Islamization of Perspective Science and Its Relevance for Islamic Education Curriculum - Dhiky Ary Wardana; Budi Haryanto (Universitas Muhammadiyah Sidoarjo, 2021)
This article aims to add scientific references about the concept of Islamization of Ismail Raji Al-Faruqi's perspective of science and its relevance to the Islamic education curriculum, so that later if anyone looks for references on the concept of Islamization of Ismail Raji Al-Faruqi's perspective of science, there can be more, thus can make it easier for readers. The type of research used is library research where the data is obtained from the literature using a philosophical approach. The results of the study found that Ismail Raji Al-Faruqi's concept of Islamization of science is with 12 active steps so that it is hoped that there will be no dichotomy. And the relevance of Ismail Raji al-Faruqi's thoughts for the Islamic education curriculum can be seen in three meaningful points which are philosophically stated so that there is relevance for the quality of the Islamic education curriculum.